Financial Conditions and Growth at Risk in the ECCU - Komatsuzaki, Takuji (IMF Working Papers; Working Paper, 2019)
We study the growth determinants in the Eastern Caribbean Currency Union (ECCU), using the Growth at Risk (GaR) framework with a focus on financial variables. We find that excessive bank credit growth is associated with lower future real GDP growth in the medium term especially on the low quantiles of growth distribution. Moreover, worsening of both global financial conditions and external conditions are associated with lower future growth in the short term, especially at the high quantiles of growth distribution. Country-specific results are broadly in line with ECCU-wide results, with some variation potentially due to the strong Citizenship-By-Investment program inflows and lack of credit union data. The establishment of a macroprudential framework in the ECCU would need to pay close attention to credit growth not only of banks but also credit unions and continue to monitor global and external conditions.